ChemInform Abstract: An Efficient One‐Pot Two Catalyst System in the Construction of 2‐Substituted Benzimidazoles: Synthesis of Benzimidazo[1, 2‐c]quinazolines. Issue 16 (March 2016) - Cimarelli, Cristina; Di Nicola, Matteo; Diomedi, Simone; Giovannini, Riccardo; Hamprecht, Dieter; Properzi, Roberta; Sorana, Federico; Marcantoni, Enrico
Abstract: A Ce(III)/Cu(I)‐catalytic system mediates the reaction of aryl‐ and alkylaldehydes (I) and (IV) with o‐phenylenediamine (II) to the title compounds in good yields.